Correlation between Adverse Childhood Experiences and Mental Well-being of Women in Emerging Adulthood - Ernawati, Linda; Augusttiarini, Prita; Yudistira P, Chandra (Universitas Mercu Buana Yogyakarta, 2022)
Adverse childhood experience (ACE) is a term used to describe traumatic events or circumstances that children may experience before the age of 18. This research aims to determine the correlation between adverse childhood experience and mental well-being of women in emerging adulthood. The subjects in this study were emerging adulthood women, totaling 219 women as the research sample. The sampling technique used was incidental sampling. The sample was based on chance. Collecting data by distributing questionnaires. The analytical technique used is chi-square analysis. The results showed that adverse childhood experiences that have a relationship with mental well-being are emotional violence, physical violence, emotional neglect, physical neglect, experiencing parental separation, seeing mother or family members being treated harshly, and living with family members who have mental disorders.